ALIH FUNGSI LAHAN PERTANIAN DAN PRODUKSI PANGAN DI KABUPATEN JEMBER - Aryo Fajar Sunartomo (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
Paddy land conversion to non-agricultural in Jember raises concerns about the threat to food security, this happens because Jember is one of the largest rice producer in East Java. The research method used descriptive, analytic and correlational. Paddy land in Jember from 2005 to 2013 has decreased land area with the average area per year amounted to 81,86 ha/year, while the land needed  for housing, facilities and services, industrial increased by 72,90 ha/year Ha, 12,10 ha/year and 4,46 ha/year. The conversion of agricultural land (paddy) in Jember over a period of 2006 to 2013 caused the decrease of rice production 4.593,09 kw with the level of reduction in production about 31,92%. In the coming period, the rice needs for the community in Jember estimated at 8.368.010 kw by the needs of the average harvested area at 519.118 Ha Keywords : land, conversion,  impact, production, rice